HUBUNGAN SELF-DETERMINATION DAN MOTIVASI BERPRESTASI DENGAN KEMAMPUAN PENGAMBILAN KEPUTUSAN SISWA SMA - Henny Christine Mamahit; Dominikus D. Biondus Situmorang (Psibernetika, 2016)
Career decision-making ability requires the ability to assess and think of the integration between the knowledge of themselves and the knowledge of the job. Self-determination is the ability to identify desire for autonomy, competence, and relation in order to achieve a target. Achievement motivation refers to students’ attempts to meet goals by becoming a moderate risk taker, showing perseverance in work, having expectation for feedback, showing responsibility in a given task, and having the ability to innovate. The objective of this research is to analyze the effect of self-determination and achievement motivation on Senior High School students’ career decision-making ability. This research also investigates if the aforementioned variables are correlated. The sample for this research are 410 students of Senior High School Grade XI. This is a quantitative based research with multiple correlational research design. The results of the research shows that the correlation value between the self-determination and achievement motivation variables and the career decision-making ability variable is 0.780 (0.00 <0.05). This means that there is a significant correlation between the aforementioned variables. The contribution of the self-determination and achievement motivation variables to the career decision-making ability  variable ((R2) is 78%. Keywords: career decision-making abilities; self-determination; achievement motivation.